Nilai Ekonomi Pengelolaan Hutan Lindung Blok Kawae KH. Maria/RTK 25 BKPH Maria Donggomasa Dinas LHK Provinsi NTB - Ahyar, Ahyar; Susanto, Agus; H, Hadian Pratama (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
One part of the Sari watershed, which was a strategic area for Bima City, was the Kawae Block protected forest area. This forest area acted as a catchment area for the Bima City Region and supports the lives of the people of Wawo, Bima Regency and its surroundings. In the last decade, the Kawae Block protected forest area has come under pressure from vulnerability in several ways, especially pressure from destruction due to illegal logging and encroachment on forest areas for farming of seasonal crops (corn). The aim of this research were to analyze the factors that directly cause damage and the economic value of damage as well as the economic value of potential natural resources in the Kawae Block Protected Forest Area. This research was conducted in the Kawae KH Block Protected Forest Area. Maria/RTK 25 BKPH Maria Donggomasa Provincial LHK Service. NTB with an area of 1,500 hectares. The sample used was 210 respondents. The variables used in this research were the price value of NTFPs and the price value of water to calculate the value of direct benefits of forest areas, ecological benefits, flood control and carbon emission reduction/carbon credits to calculate the value of indirect benefits of areas and the value of biodiversity to calculate the value of selected benefits. Data analysis was carried out for regional economic valuation using the total economic value valuation method (Total Economic Value). The research resulted in the factors that directly cause damage to the area; they were land burning, encroachment on areas for agricultural land for seasonal crops/corn, excessive community management, rosewood theft/illegal logging and opening of farming roads. Meanwhile, the total economic value of the HL Kawae Block area was IDR. 61,135,306,500,-. The economic value resulting from sustainable forest management is much more profitable than the results of cultivating seasonal crops (especially corn).